In Idi Amin's shadow : women, gender, and militarism in Uganda - Decker, Alicia C. (New African histories series., 2014)
In Idi Amin;s Shadow is a rich social history examining Ugandan women's complex and sometimes paradoxical relationship to Amin's military state. Based on more than one hundred interviews with women who survived the regime, as well as a wide range of primary sources, this book reveals how the violence of Amin's militarism resulted in both opportunities and challenges for women. Some assumed positions of political power or became successful entrepreneurs, while others endured sexual assault or experienced the trauma of watching their brothers, husbands, or sons "disappeared" by the state's security forces. In Idi Amin's Shadow considers the crucial ways that gender informed and was informed by the ideology and practice of militarism in this period. By exploring this relationship, Alicia C. Decker offers a nuanced interpretation of Amin's Uganda and the lives of the women who experienced and survived its violence. Each chapter begins with the story of one woman whose experience illuminates some larger theme of the book. In this way, it becomes clear that the politics of military rule were highly relevant to women and gender relations, just as the politics of gender were central to militarism. By drawing upon critical security studies, feminist studies, and violence studies, Decker demonstrates that Amin's dictatorship was far more complex and his rule much more strategic than most observers have ever imagined.--Amazon.com